Bile duct kinking after adult living donor liver transplantation: Case reports and literature review. Issue 10 (October 2015) - Wan, Ping; Xia, Qiang; Zhang, Jian Jun; Li, Qi Gen; Xu, Ning; Zhang, Ming; Chen, Xiao Song; Han, Long Zhi
Abstract : Regeneration of the partial allograft and the growth of children may cause kinking of the biliary tract after pediatric living donor liver transplantation (LDLT), but bile duct kinking after adult LDLT is rarely reported. We herein presented two patients who suffered from anastomotic strictures caused by severe bile duct kinking after LDLT. The first patient was a 57‐year‐old woman with hepatitis B virus (HBV)‐related liver cirrhosis, who developed biliary stricture 5 months after receiving right‐lobe LDLT. Subsequently, endoscopic and percutaneous treatments were attempted, but both failed to solve the problem. The second was a 44‐year‐old woman also having HBV‐related liver cirrhosis. Biliary stricture occurred 14 months after LDLT. Likewise, the guide wire failed to pass through the stricture when endoscopic interventions were conducted. Afterwards, both of the two cases underwent reexploration, showing that compensatory hypertrophy of the allografts resulted in kinking and sharp angulation of the bile ducts, and the anastomotic sites were found to be severely stenotic. Finally, re‐anastomosis by Roux‐en‐Y procedure was successfully performed, and long‐term stenosis‐free survival was achieved in both of them. Our experience suggests that bile duct kinking after LDLT may play a role in the high incidence of anastomotic strictures in adult LDLT recipients, which may also result in the treatment failure of the non‐surgical techniques for anastomotic strictures. Re‐anastomosis in the form of Roux‐en‐Y hepaticojejunostomy is an effective surgical option for the treatment of such a condition.